Complete Colonic Duplication and Perineal Fistula: Transanal Mucosectomy of the Ectopic Rectum - Johannes W. Duess; Peter Zimmermann; Franz W. Hirsch; Daniel Graefe; Martin Lacher; Jan-Hendrik Gosemann (Georg Thieme Verlag KG, 2022)
Background Colonic duplication may present in different anatomic variants. The surgical approach towards these anomalies can be challenging and has implications for subsequent future continence. Case Description We report on a 1-year-old girl with congenital heart defect and pacemaker who was referred to us with an anorectal malformation. The patient was stooling from both an anus and a perineal fistula. Examination under anesthesia revealed an orthotopic and age-appropriate sized anus with surrounding sphincter and a second rectal lumen ending as a perineal fistula. A computed tomography and contrast enema indicated colonic duplication. Exploratory laparotomy showed a duplicated terminal ileum leading to two ceca and appendices, which joined to a duplicated colon with a septum and common mesentery. At the rectosigmoid junction, one part of the duplication ended as a perineal fistula, the second one led to the (orthotope) anus. The common colonic wall was divided using a stapler. The rectal duplication leading to the perineal fistula was not completely resected but treated by mucosectomy only (Soave plane) leaving its muscular cuff in place. Finally, an ileostomy was created. The postoperative course was uneventful. A contrast enema prior to ostomy takedown demonstrated a well-configurated colon and rectum without stenosis or impaction. The girl is currently continent with a complete resolution of her constipation. Conclusion In cases of complete colonic duplication division of the common wall is simple and safe. Mucosectomy of the ectopic rectum limits pelvic dissection and preserves the entire muscular wall of the duplicated orthotope rectum.